A desconstrução da educação iluminista em Heinrich von Kleist - Silva, Carina Zanelato [UNESP] (2019)
The Enlightenment pedagogy aimed to discuss the means of educating the human being both for good and intellectual independence, based on the principles of moral laws and of the supreme good. Thus, philosophy at that time has set the total responsibility of man for his acts as a parameter of its pedagogy, which entailed the indispensability of an education that has undergone a positive transformation in human nature, based on the maxim of moral judgement. Initially adept at such proposal, Heinrich von Kleist, right after his famous Kantian crisis, began to contest the Enlightenment education model from a skeptical bias, since, for the author, the Kantian criticism showed the failures of this pedagogy according to a new view of reality. From this new perspective, the notions of freedom and morality assumed a new characterization, since it became impossible for Kleist to determine the results of these educational projects on human conduct. In face of this scenario, we will analyze in this paper two exemplary texts of how the author transposes such discussion into literature: in Allerneuster Erziehungsplan, Kleist inverts the logic of this education by proposing a school of vice, whereas in Der Findling, the author contests the bourgeois moral values of family and supreme good, leading to a text full of violence and evil.